2019
DOI: 10.1093/cid/ciz438
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Tuberculosis and Effect of Preventive Therapy Among Close Contacts of Persons With Infectious Tuberculosis

Abstract: Background Close contacts of persons with pulmonary tuberculosis (TB) have high rates of TB disease. Methods We prospectively enrolled TB patients and their close contacts at 9 US/Canadian sites. TB patients and contacts were interviewed to identify index patient, contact, and exposure risk factors for TB. Contacts were evaluated for latent TB infection (LTBI) and TB, and the effectiveness of LTBI treatment for preventing con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 18 publications
0
25
0
4
Order By: Relevance
“…6,8,[12][13][14][15][16] There are also a clinical and an animal study which reported increased values of BMD, vitamin D and bone formation markers after treatment with LEV. 17,18 Moreover, reduced bone strength without any alteration in BMD values due to LEV treatment was also reported by Nissen-Meyer et al 19 The study of Nissen-Meyer et al reported the possibility of LEV to affect the collagen-rich matrix of bone independently from BMD without any significant change in the mineral structure. 19 The investigation of the side-effects of LEV on both bone mineral and matrix independently from each other would be helpful to reveal the different effects of the drug on bone structure.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…6,8,[12][13][14][15][16] There are also a clinical and an animal study which reported increased values of BMD, vitamin D and bone formation markers after treatment with LEV. 17,18 Moreover, reduced bone strength without any alteration in BMD values due to LEV treatment was also reported by Nissen-Meyer et al 19 The study of Nissen-Meyer et al reported the possibility of LEV to affect the collagen-rich matrix of bone independently from BMD without any significant change in the mineral structure. 19 The investigation of the side-effects of LEV on both bone mineral and matrix independently from each other would be helpful to reveal the different effects of the drug on bone structure.…”
mentioning
confidence: 67%
“…6 In contrast to our studies, Karesova et al reported increased BSAP and CTX of type I collagen markers in Wistar rats after twelve weeks of LEV treatment. 18 In summary, alterations in PTH and 1,25(OH) 2 D amounts in LEV-treated rats might stimulate bone turnover by increasing bone formation and reducing bone resorption. In epileptic rat group, a low amount of 1,25(OH) 2 D might cause reduced bone formation due to insignificant alteration in PTH amounts.…”
Section: Discussionmentioning
confidence: 90%
“…A total of 51 index cases were recruited, median (IQR) age of 21 (20)(21)(22)(23) years and 31 (61%) were males. 156 contacts were screened, median (IQR) age of 23 (20)(21)(22)(23) years, 80 (51%) were males and 76 (49%) were household contacts. Among the 156 TB contacts, 5 participants were con rmed positive for TB: prevalence of 3.2% (95% CI 1.0 to 7.3%).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a study of risk factors for TB among close contacts reported that sharing a bedroom with an index case increased exposure to TB perhaps due to enhanced contact during the night, shared airspace, and sharing of MTB aerosols [21]. Our ndings were also consistent with earlier studies where the risk of transmission was reported to be related to the duration and proximity of contact with the source case, being in an enclosed space with the source case and the infectivity of the source case [21][22][23]. Those who shared a bed likely spent the most time with the patient during their period of infectivity (usually weeks to months before diagnosis) hence at the highest risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…According to some epidemiological studies, an increased risk of infection is related to activities that involve close contact with TB patients and work in which aerosol-generating procedures (AGPs) are used. Workplaces with AGP, work duration, room size, and priority of contact with TB were also reported to be related to LTBI [14,[19][20][21][22][23][24][25][26][27][28][29]. Although medical activities are known to be a risk and ineffective prevention, poor immunity (i.e., lack of an adequate Bacille Calmette-Guérin (BCG) vaccine) is considered a greater risk for having LTBI [20].…”
Section: Introductionmentioning
confidence: 99%